Revealing Minor Electrical Losses in the Interconnecting Layers of Organic Tandem Solar Cells - Prosa, Mario; Li, Ning; Gasparini, Nicola; Bolognesi, Margherita; Seri, Mirko; Muccini, Michele; Brabec, Christoph (Advanced Materials Interfaces, 2017)
The interconnection layer (ICL) of organic multijunction solar cells represents one of the most delicate parts to ensure an efficient device operation. In view of pushing the efficiencies toward the theoretical limit, the individuation of minor losses affecting the ICL operation is of crucial importance. However, the difficulties arising from its position within the complex device structure typically hamper an accurate and selective investigation of the ICL. Here, a method based on the analysis of the photo-generated current density-voltage (Jph-V) response of solar cells, in the region of bias over the open-circuit voltage, is proved to individuate minor electrical losses within the ICL. Interestingly, the proposed method is demonstrated to effectively operate on tandem substructures, where different ICLs are investigated through the combination of materials having diverse characteristics. Furthermore, the use of a complementary investigation technique based on electroluminescence (EL) analysis allows to distinguish the specific nature of the electrical losses. The combination of Jph-V and EL analyses represents an elegant and advanced approach to shed light on the quality of ICLs in tandem substructures by avoiding the fabrication of the more complex tandem architecture. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Electrical losses; Electroluminescence; Interconnecting layers; Organic tandem solar cells; Photo-generated current